Internalization Values of Character Education As a Solution for Degradation of Civility of the Nation - Abd. Chaidir Marasabessy; Suanto; Eti Hayati; Sri Utaminingsih (Jayapangus Press, 2022)
This research is motivated by various phenomena of moral decadence that result in immoral behavior, such as corrupt behavior, sexual harassment, sadistic murder and so on. The study of character education is felt to be very urgent to answer these various phenomena. This research aims to describe the importance of internalizing the values ​​of character education as a solution to the nation's civilization. This study uses a qualitative approach, while data processing is carried out through a literature review. In order to answer immoral behavior, the application of character education must be based on religious values, law, culture, decency, and decency, which are internalized through education, experience, and experimentation. The results of the research indicate that it is necessary to internalize the values ​​of character education, both at the level of formal and informal education, so that universally the role of each element in society is the foundation in shaping the nation's character. Thus, there are three things that can be done in character building as a solution to the degradation of national civilization, namely; 1) Building an example for the nation's elite, 2) Empowering educators, and 3) Supporting the social, cultural, and religious environment.